2010
DOI: 10.1177/1010539510361787
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of On-Reserve Road Versus Off-Reserve Road Motor Vehicle Crashes in Saskatchewan, Canada

Abstract: Factors from all 3 levels (human, environmental, and vehicle factors) are associated with on-reserve MVCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…There was however no statistically significant association for those that sustained severe injuries. Findings from other studies revealed that those that had used alcohol were more likely to sustain less severe injuries compared to those that did not (Liu, Liang, Rau, Shiun-Yuan , & Hsieh, 2015) and higher BAC levels led to less severe injuries (Mann, Desapriya, Fujiwara, & Pike, 2011). Pre-injury alcohol use was however associated with death at the ED when compared to those who were treated and sent home.…”
Section: Nature and Severity Of Injurymentioning
confidence: 97%
See 2 more Smart Citations
“…There was however no statistically significant association for those that sustained severe injuries. Findings from other studies revealed that those that had used alcohol were more likely to sustain less severe injuries compared to those that did not (Liu, Liang, Rau, Shiun-Yuan , & Hsieh, 2015) and higher BAC levels led to less severe injuries (Mann, Desapriya, Fujiwara, & Pike, 2011). Pre-injury alcohol use was however associated with death at the ED when compared to those who were treated and sent home.…”
Section: Nature and Severity Of Injurymentioning
confidence: 97%
“…In contrast, there are people who are disadvantaged because of their association with ethnic minority groups. Evidence suggests that young drivers with ADHD (Curry, Yerys, Metzger, Carey, & Power, 2019;Jerome, Segal, & Habinski, 2006), a mental disability (Brooks, Mossey, Tyler, & Collins, 2014) or a member of minority ethnic group such as indigenous Australians (Cercarelli, 1994;Cercarelli & Knuiman, 2002;Clapham, Senserrick, Ivers, Lyford, & Stevenson, 2008), indigenous Canadians (Desapriya, Fujiwara, Verma, Babul, & Pike, 2011) and Maoris (Sargent et al, 2004) have an increased risk of crashing or other negative driving outcome.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These variables included the earliest initial post-resuscitation Glasgow Coma Scale score, specific use of protective equipment (seatbelt or helmet), polytrauma status (defined as traumatic injury to a body region besides the head), comorbidity status (2 or more of diabetes mellitus, dyslipidemia, hypertension, coronary artery disease, history of stroke or psychiatric illness), use of rehabilitation services and any status of intoxication with alcohol (as reported by the chart note of the first physician assessment). We classified the severity of injury based on the earliest recorded Glasgow Coma Scale score after resuscitation: mild (score of [3][4][5][6][7][8][9][10][11][12][13][14][15], moderate (9)(10)(11)(12) or severe (3)(4)(5)(6)(7)(8). 24 We assessed functional outcomes using the first Glasgow Outcome Scale scores at least 6 months after the injury.…”
Section: Measured Variablesmentioning
confidence: 99%
“…[7][8][9][10] These populations have different risk factors related to the occurrence of trauma compared with other Canadians. [11][12][13][14] Given that the determinants of traumatic brain injury and patient outcomes differ between indigenous populations, surveillance conducted on a community-specific basis can provide evidence that informs relevant prevention strategies for these communities. 3,15 However, most surveillance efforts are conducted at the larger jurisdiction level.…”
mentioning
confidence: 99%